Application of organic fungicide in controlling basal stem rot disease for mature oil palm - Happy WIDIASTUTI; Hayati MINARSIH; Djoko SANTOSO; Deden Dewantara ERIS; Galuh Wening PERMATASARI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2020)
Ganoderma is a major pathogen in oil palm crops. Some efforts related to control the growth of Ganoderma have been conducted but still have not found an effective method. This study aims to develop an organic fungicide that has been tested in vitro, which effective in controlling the growth of Ganoderma. The optimization carried out includes the determination of the dose and time interval for application in 13-year-old mature oil palm. This organic fungicide application was the continuation of application during the previous year especially for the two best treatment which is application organic fungicide every week (1w) and every two weeks (2w). In this study, the treatments tested were three levels dose of organic fungicide (0, 1x and 2x) and two types of frequency application, i.e. every week (1w) and every other week (2w). The results showed that the best application of organic fungicides was every week application with twice doses (1w.2x), based on the parameters of the inhibition of Ganoderma’s fruiting body formation, primary and secondary root formation, the opening of spear leaves, and harvesting parameters. The application of organic fungicide able to recover the oil palm infected Ganoderma sp., with increasing the fresh fruit bunch and its weight around 70% and 78%, respectively.